„Multicultural training” for university teachers teaching foreiner students : Initiative by SZIU Faculty of Economics and Social Sciences, which coordinates the foreigner students’ expectations and educational characteristics in our university - Rudnák, Ildikó; Komor, Levente; Józsa, Imola (Studia Mundi – Economica, 2015)
We have explored the theoretical and test results of a multicultural training organized for teachers of an educational institution at Szent István University. Actuality provides a growing number of foreign students, which means not only an increase in the number of classes taught in English, but proper preparation of the human resources of the institution as well. After analyzing the training we propose to all eviate the problems, forming the diversity advantage, exploit opportunities inherent in multiculturalism.